Rents, Experiments, and the Perpetual Presence of Concessionary Weather Insurance - Johnson, Leigh (Annals of the American Association of Geographers, 2022)
Geographers have interpreted the rise of weather insurance for small agricultural producers as emblematic of financialization's inexorable march to capitalize the countryside. Yet this market has proved far less successful than advocates hoped or critics feared. Rather than a speculative tool for surplus extraction from smallholders or a mechanism for their financial subjectification, this article reinterprets weather insurance as an infrastructure of concessionary transfers from the development sector to make market-mediated mechanisms work. These transfers are emblematic of the new distributional terms struck between donors, states, and insurance capital as financial risk transfer is articulated with the extension of fragmentary safety nets. Economic field experiments with insurance have proliferated as venues in which the value of insurance is tested by both economists and experimenting subjects. Just as data from these trials have suggested some positive welfare impacts, they have also indicated target clients are unwilling or unable to pay full market price, thus performing a new justification for the perpetual presence of subsidies. Such transfers present opportunities for reinsurers to command rents through their control of large pools of capital and their interpretive authority over techniques for pricing risk under uncertainty. In a changing climate, reinsurers are poised to collect larger rents from donors' and governments' premium subsidies meant to decrease insurance costs for the vulnerable. These dynamics of rent cycling underscore the urgency of building more equitable, systematic risk-sharing infrastructures to replace the current fragmentary archipelagos of weather insurance.